2013
DOI: 10.1021/nl4030193
|View full text |Cite
|
Sign up to set email alerts
|

Single Crystalline Nanostructures of Topological Crystalline Insulator SnTe with Distinct Facets and Morphologies

Abstract: Topological crystalline insulators (TCIs) are a new class of topological materials that possess unique metallic surface states protected by crystalline mirror symmetry. Their topological surface properties are expected to strongly depend on the surface orientation. By combining density functional theory (DFT) calculations and synthesis experiments, we demonstrate the controlled growth of single crystalline nanostructures of the prototypical TCI SnTe with distinct facets and morphologies. Our calculations sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
101
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(118 citation statements)
references
References 37 publications
(56 reference statements)
12
101
2
3
Order By: Relevance
“…This suggests that the surface energy for our growth conditions is the lowest for the growth along the [100] direction, becoming slightly higher for the [111] and much higher for the [110] directions, which is consistent with the conclusion on the preferential growth orientation in SnTe crystalline nanostructures reported in Ref. (29). It is worth noting that the surface energies have indeed been predicted to be determinants for particle morphology; 32 in this regard, SnTe nanostructures are a useful playground for nanomorphology.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that the surface energy for our growth conditions is the lowest for the growth along the [100] direction, becoming slightly higher for the [111] and much higher for the [110] directions, which is consistent with the conclusion on the preferential growth orientation in SnTe crystalline nanostructures reported in Ref. (29). It is worth noting that the surface energies have indeed been predicted to be determinants for particle morphology; 32 in this regard, SnTe nanostructures are a useful playground for nanomorphology.…”
Section: Resultssupporting
confidence: 91%
“…[26][27][28][29][30] In particular, SnTe nanoplates with both {100} and {111} surfaces were successfully grown using Au catalyst, but without the catalyst, only nanoblocks of SnTe were reported to grow. 30 Here, we report the growth of Sn1-xInxTe nanoplates with {100} and {111} Figure 1a.…”
Section: Introductionmentioning
confidence: 99%
“…Soon after the discovery of SnTe a bulk TCI, several methods to grow SnTe nanostructures by vapor transport with Ar gas flow with/without a gold catalyst were reported [31][32][33][34][35][36]. These suggested that In-SnTe nanostructures can be made available with similar growth methods.…”
Section: Introductionmentioning
confidence: 99%
“…[26] and at a relatively higher temperature than that of the VTG with Ar gas flow [31][32][33][34][35]37]. However, the actual dimensions of In-SnTe nanorods/nanowires grown without any catalyst materials on a Si/SiO 2 substrate in an evacuated quartz glass tube are often too thick to be a one-dimensional object with a single conduction channel.…”
Section: Introductionmentioning
confidence: 99%
“…Rotational symmetries in particular yield multiple mirror planes, and connect distinct surface Dirac cones to one another, yielding a multiplicity of easy axis directions. For sufficiently high symmetry, all the surface Dirac points may be related by symmetry operations, resulting in a fully gapped surface spectrum and a large number of groundstate orientations.To illustrate this physics, we present detailed calculations for the (111) surface of (Sn,Pb)Te [8,[20][21][22], using a known model Hamiltonian [3,23]. The (111) surface states are characterized in this system by four surface Dirac points, one at theΓ point and one at each of three Fig.…”
mentioning
confidence: 99%